Fundamentals of environmental engineering - Mihelcic, James R. (John Wiley, 1999)
Develop a better understanding of what causes environmental problems and how to solve them! Today, engineers and scientists must work on more complex environmental problems than ever before. To find solutions to these problems requires an in-depth knowledge of the fundamentals of chemistry, biology, and physical processes. This text will provide you with a clear explanation of these fundamentals that are necessary for solving both small town and global environmental problems. With Fundamentals of Environmental Engineering, you'll develop a better understanding of the key concepts required for design, operation, analysis, and modeling of both natural and engineered systems. You'll also be able to make connections among the different specialty areas of environmental engineering emphasized throughout the text. And you'll quickly learn how to solve complex environmental problems and incorporate environmental concerns into your specialty. Key Features * Covers the fundamentals of chemical, physical, and biological processes, and various units of concentration as applied to environmental engineering. * Includes applications related to drinking water and wastewater treatment, air quality engineering and science, groundwater transport and remediation, surface water quality, hazardous solid waste management, and ecosystems. * Developed by a team of authors who specialize in a diverse set of environmental areas.